Conocimiento, conciencia y actitudes en la conservación de los recursos pesqueros en la Reserva Nacional Allpahuayo Mishana. Iquitos, 2024 - Ahuanari Diaz, Jehu (2025)
The exploratory, descriptive and non-experimental cross-sectional design study analyzed the knowledge of four communities in the Allpahuayo Mishana National Reserve about the conservation of fishing resources and its relationship with management practices. With a sample of 60 residents, the results showed a high level of knowledge about conservation, but with variations in the implementation of sustainable practices. Socioeconomic, cultural and educational factors influence these practices, highlighting the need for environmental awareness and education. It is recommended to strengthen participatory mechanisms, integrate ancestral knowledge and promote sustainable practices to improve the conservation of aquatic ecosystems.